Mapping, Countermapping, and Country in Trace Balla’s Graphic Novels - Melanie Duckworth (Barnelitterært Forskningstidsskrift)
This article argues that the maps in Australian author and illustrator Trace Balla’s graphic novels visualize the process of meeting and forming a relationship with Country. Mapping is an integral component of Rivertime (2014), Rockhopping (2016), and Landing with Wings (2020), as the child characters draw and record their movements through and relationships with the land, and its human and nonhuman inhabitants. The article builds on recent work on mapping in children’s literature, postcolonial approaches to mapping and countermapping, ecocriticism, and Indigenous epistemologies, particularly the concept of “Country”. I suggest that Balla’s graphic novels decolonize the act of mapping and envision a less invasive, more respectful relationship with Australian landscape, plants, and animals by mapping children’s perspectives in conversation with Indigenous Australians.